Mekanik ventilatöre bağlı hastalarda hastane içi taşınmaya bağlı komplikasyonların önlenmesi - Çelik, Sevim; Kanan, Nevin; Çelik, Sevim (My University, 2003)
Mekanik ventilatöre bağlı yoğun bakım hastaları- nın hastane içinde diğer bölümlere taşınmaları sı- rasında komplikasyon gelişme olasılığı çok yük- sektir. Bu durum, hastaya bağlı etkenlerden ve ta- şınma öncesinde hazırlığın, taşınma sırasında da hasta izleminin yetersiz yapılmasından kaynak- lanmaktadır. Komplikasyon gelişimini en aza indir- mede standartların/politikaların geliştirilmesi, ven- tilatöre bağlı hastalarda manuel oksijen desteği yerine taşınabilir ventilatörlerin kullanılması, yo- ğun bakım ünitelerinde uygulanabilecek alternatif tanılama ve tedavi edici teknik ya da yöntemlerin geliştirilmesi etkili olacaktır

The risk for complications during transfer ofmechanically ventilated patients to other depart-ments within the hospital is considerably high.Complications may not only result from patient-related factors but also from shortcomings in thepreparation of, and in the monitoring of patientsduring, transfer. Undesirable transfer-relatedevents may be effectively reduced through theestablishment of standard guidelines and protocols,the use of a portable ventilator instead of a manualone, and the development of alternative diagnosticand therapeutic modalities or techniques in inten-sive care units.
The prevention of complications during intrahospital transport of mechanically ventilated patients
Keywords: Kritik bakım; Kritik hastalık; Yoğunbakım ünitesi; Monitörizasyon; Hasta taşınması; Solunum; Risk yönetimi; Critical care; Critical illness; Intensive care unit; Monitoring; Patient transport; Respiratory; Risk management